Research on the Construction of Subject Group English Corpus Based on Computer Network Informatization - Zhang, Xiaozhu (Journal of physics. Conference series, 2021)
There are many English teaching resources in China. However, the quality of English resources can not be guaranteed. In recent years, we have been emphasizing the network of English teaching. Experts believe that the utilization rate of online English teaching resources is very high. Teachers can use the corpus resources in the network to find suitable teaching materials. This kind of teaching mode greatly enhances the students’ interest[1]. The construction of subject group English corpus which is easy to use in computer network has become a hot topic in English academic circles. This paper describes the concept and attributes of corpus. Finally, this paper puts forward the future direction of corpus construction.